STRATEGI PENGEMBANGAN SUMBERDAYA MANUSIA DI ERA PERSAINGAN INDUSTRI MEDIA - Saniyah, Salsabillah Putri; Kurniawati, Desi Tri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The competition in the media industry in the digital disruptive era is getting tougher, including KG Media as one of the players in the media industry that is quite calculated. Therefore, human resources are needed who have technical skills, human skills, and managerial skills. This can be done through continuous training. This research is a qualitative research with a descriptive approach that aims to analyze the employee development program implemented by KG Media. Collecting data from this study using observation and documentation techniques. The results of this study indicate that the development of human resources at KG Media in the